Sequential alcohol oxidation/putative homo Claisen–Tishchenko-type reaction to give esters: a key process in accessing novel biologically active lactone macrocycles. Issue 68 (4th July 2016) - Viana, Hugo; Carreiro, Elisabete P.; Goth, Albertino; Bacalhau, Patrícia; Caldeira, Ana Teresa; Martins, Maria do Rosário; Burke, Anthony Joseph
Abstract : We report an efficient methodology for the direct oxidative esterification of primary alcohols to diether-esters using pyridinium chlorochromate (PCC). Abstract : We report an efficient methodology for the direct oxidative esterification of primary alcohols to diether-esters using pyridinium chlorochromate (PCC). Numerous studies were carried out to probe the reaction mechanism and at the same time optimize the reaction conditions. The reaction could be conducted with 1 equivalent of PCC and 1 equivalent of BF3 ·OEt2 . Indications based on literature precedent were that the reaction may proceed via a sequential alcohol oxidation to the aldehyde followed by a putative Cr or boron catalyzed Claisen–Tishchenko-type reaction. Using this efficient methodology, we synthesized a family of novel diether-esters in very good yields; some of these molecules were subsequently tested against both acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). In addition, we also disclose a new synthetic strategy for the synthesis of lactam macrocycles with potential biological activity. This methodology included the regioselective borylation of the ester substrate and a subsequent Suzuki–Miyaura coupling to obtain the desired lactam macrocycle.